Psychometric Evidence for Chronic Stress Patient-Reported Outcome Measures in African American Adults: An Equity-Focused COSMIN Systematic Review - Michelle F. Robinson; Clifton Addison; Mariana Sanchez; Noel C. Barengo; Olatokunbo Osibogun; Jessy G. Devieux; Gira Ravelo; Derrick Amoah; Joe F. Coleman; Gequasha Collins; Elena Bastida (Journal of Racial and Ethnic Health Disparities, 2026)
Abstract Introduction Chronic stress is a well-documented psychosocial driver of cardiovascular disease (CVD) disparities disproportionately affecting African American adults, yet the psychometric adequacy of patient-reported outcome measures (PROMs) in this population remains unexamined. This systematic review evaluated the scientific evidence on the psychometric quality of chronic stress PROMs in a racially specific population at elevated cardiovascular risk. Methods PubMed/MEDLINE, Embase, CINAHL, and PsycINFO were searched (January 2000 to December 2025). Eligible studies reported psychometric properties of chronic stress PROMs in African American adults. Two reviewers independently screened studies, extracted data, and assessed methodological quality using the COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN) Risk of Bias checklist. Evidence quality was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Protocol registration: (OSF: https://osf.io/sn73g ). Results Of 2,581 records identified, 1,781 were screened after duplicate removal; five studies evaluating five instruments met inclusion criteria: the Perceived Stress Scale-10 (PSS-10) and four race-specific PROMs. All instruments demonstrated acceptable internal consistency (total scale α = 0.83 to 0.89; subscale α = 0.70 to 0.94) and partial structural validity. No instrument achieved a COSMIN Category A recommendation, as content validity was not established for any instrument and evidence for responsiveness, measurement error, and measurement invariance was absent or limited. Conclusions Psychometric gaps constrain the equitable use of chronic stress PROMs in African American adults and undermine the capacity to monitor stress-related CVD disparities. Validation studies prioritizing community-engaged content validity, responsiveness, and measurement invariance are needed to advance measurement equity for prevention.